2020
DOI: 10.1002/nop2.533
|View full text |Cite
|
Sign up to set email alerts
|

Social support predicted quality of life in people receiving haemodialysis treatment: A cross‐sectional survey

Abstract: Aims To examine levels of social support and quality of life (QOL) and to examine the association between social support and QOL in patients receiving haemodialysis (HD) treatment. Design A cross‐sectional study. Method social support and QOL were measured using the Multidimensional Scale of Perceived social Support (MSPSS) and the World Health Organization QOL‐BREF questionnaires, respectively. A convenience sample of 195 patients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
4
33
0
4
Order By: Relevance
“…According to Axelsson et al, (2020) said that family support is very influential on patient compliance in undergoing hemodialysis therapy so that it affects their quality of life. According to (Alshraifeen et al, 2020) social support and age as factors that affect the quality of life of hemodialysis patients and as a suggestion from this study is the concern of the hemodialysis unit for social support for this disease group. Thus, one of the factors that can affect the quality of life is social support.…”
Section: Introductionmentioning
confidence: 71%
“…According to Axelsson et al, (2020) said that family support is very influential on patient compliance in undergoing hemodialysis therapy so that it affects their quality of life. According to (Alshraifeen et al, 2020) social support and age as factors that affect the quality of life of hemodialysis patients and as a suggestion from this study is the concern of the hemodialysis unit for social support for this disease group. Thus, one of the factors that can affect the quality of life is social support.…”
Section: Introductionmentioning
confidence: 71%
“…The role of non-pharmacological management of mental health conditions is gaining support within renal medicine [33], but this is slow to fruition within practice. Recent evidence shows perceived social support is also an important factor in patients' ability to cope with their illness and can improve well-being [34]. Therefore, novel interventions that maintain or improve social well-being, including social support, social participation and relationships, may help improve quality of life for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear relationship between the care satisfaction and quality of life of dialysis patients, making the healthy interaction between the patient and health care providers crucial in any dialysis unit [ 24 ]. Another essential factor that plays a significant role in HD patients’ psychology is social support [ 25 , 26 ]. It has been demonstrated that low perceived social support leads to poor quality of life in HD patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another essential factor that plays a significant role in HD patients’ psychology is social support [ 25 , 26 ]. It has been demonstrated that low perceived social support leads to poor quality of life in HD patients [ 26 ]. On the other hand, social support from family seems to be an effective therapy for anxiety, depression, and other psychological disorders in HD patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%